Role of autophagy-related protein expression in patients with rectal cancer treated with neoadjuvant chemoradiotherapy. Issue 1 (December 2016) - Shim, Byoung; Sun, Der; Won, Hye; Lee, Myung; Hong, Soon; Jung, Ji-Han; Cho, Hyeon-Min; Ko, Yoon
Abstract Background Autophagy, a cellular degradation process, has complex roles in tumourigenesis and resistance to cancer treatment in humans. The aim of this study was to explore the expression levels of autophagy-related proteins in patients with rectal cancer and evaluate their clinical role in the neoadjuvant chemoradiotherapy setting. Methods All specimens evaluated were obtained from 101 patients with colorectal cancer who had undergone neoadjuvant chemoradiotherapy and curative surgery. The primary outcomes measured were the expression levels of two autophagy-related proteins (microtubule-associated protein 1 light chain 3 beta (LC3β) and beclin-1) by immunohistochemistry and their association with clinicopathological parameters and patient survival. Results Among the 101 patients, the frequency of high expression of beclin-1 was 31.7 % (32/101) and that of LC3β was 46.5 % (47/101). A pathologic complete response was inversely associated with LC3β expression (P = 0.003) and alterations in the expression of autophagy-related proteins (P = 0.046). In the multivariate analysis, however, autophagy-related protein expression did not show prognostic significance for relapse-free survival or overall survival. Conclusions High expression of autophagy-related proteins shows a strong negative association with the efficacy of neoadjuvant chemoradiotherapy in patients with rectal cancer. Autophagy has clear implications as a therapeutic target with which to improve the efficacy of neoadjuvant chemoradiotherapy.